Efficacy of Topical Estradiol Compared to Topical Glycolic Acid for Skin Aging Treatment in Postmenopausal Women - Yusharyahya, Shannaz Nada; Bianti, Marsha (Journal of General - Procedural Dermatology and Venereology Indonesia, 2017)
Skin aging is a complex biological process in human being, as a result from intrinsic factors (genetic, hormonal, metabolism) and extrinsic factors (UV exposure, pollution, smoking, life style). In postmenopausal women, physiologically, the amount of estrogen are decreased, causing deterioration of their skin’s appearance. Along with the changes that occur, skin care require more attention. A holistic approach can increase epidermal thickness, therefore, reducing the depth of wrinkles, as well as improving skin texture and moisture. There are various treatments available to improve skin appearance due to aging. This EBCR is aimed to compare the efficacy of topical estradiol and topical glycolic acid as skin treatment in postmenopausal women. Articles were searched through Pubmed/MEDLINE, EBSCO, and Cochrane. One randomized-controlled trial by Fuchs KO, et al was obtained and critically appraised. Based on the appraisal, study by Fuchs KO, et al is considered valid, important, and applicable. Both estradiol and glycolic acid show good efficacy and safety for postmenopausal women with signs of skin aging, however estradiol is not considered to have better efficacy than glycolic acid.